Managing Broadcasting and Film Arts Expertise Programs to Improve Graduate Competency in Vocational Education - Indanarti, Indanarti; Abdullah, Ghufron; Nugroho, Aryo Andri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to examine and analyze the implementation of management strategies in the Broadcast and Filmmaking Skills Program at SMK Negeri 1 Kendal to improve graduate competency. The research emphasizes four core management functions: planning, organizing, actuating, and controlling, along with evaluation processes that enhance graduate readiness for employment, higher education, and entrepreneurship. A qualitative phenomenological approach was employed to explore the lived experiences and subjective perspectives of key stakeholders involved in managing the program. Participants included the principal, vice principals, head of the skills program, productive subject teachers, students, alumni, and industry partners (DUDIKA). Data were collected through in-depth interviews, participatory observations, and document analysis. Analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing with ongoing verification. The findings reveal that management implementation in the Broadcast and Filmmaking Skills Program is adaptive and context-responsive, aiming to achieve productivity, stakeholder satisfaction, and sustainable graduate pathways. Participatory planning engages school stakeholders and industry partners to address limited employment opportunities and diverse student potential by strengthening entrepreneurial orientation and curriculum relevance. Organizing is carried out through clear team structures, systematic task distribution, and a semi-block scheduling system, while strong industry collaboration ensures alignment between competencies and labor market demands. Actuating is implemented through deep learning and project-based learning approaches that develop both technical and interpersonal skills. Controlling is conducted systematically through tiered supervision, digital monitoring systems, and innovative student manager roles, supporting continuous quality improvement and graduate competitiveness.